Hamlet and Japanese Men of Letters - Kawachi, Yoshiko (Multicultural Shakespeare: Translation, Appropriation and Performance, 2016)
Shakespeare has exerted a powerful influence on Japanese literature since he was accepted in the second half of the nineteenth century. Particularly Hamlet has had a strong impact on Japanese men of letters and provided them with the impetus to revive the play in contemporary literature. In this paper I discuss how they have utilized Hamlet for their creative activity and enriched Japanese literature.